2014
DOI: 10.1111/auar.12060
|View full text |Cite
|
Sign up to set email alerts
|

Productivity Analysis of UK Auditing Firms

Abstract: This study analyses the productivity change in the United Kingdom (UK) of auditing firms over the period [2005][2006][2007][2008][2009][2010][2011][2012], using a Malmquist index with a technological bias. Productivity is the rate at which goods or services are produced relative to the input. A common measure of productivity is the ratio of output per unit of labour used in the production. Productivity change is the change in the total output relative to the change in the total input and it is composed of tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Barros et al. () assess the efficiency of audit firms in the United Kingdom (UK) using DEA. Hsiao et al.…”
Section: Theoretical Underpinnings and Prior Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Barros et al. () assess the efficiency of audit firms in the United Kingdom (UK) using DEA. Hsiao et al.…”
Section: Theoretical Underpinnings and Prior Studiesmentioning
confidence: 99%
“…Rodriguez-Perez et al (2011) apply DEA to assess the impact of fair value accounting in financial statement analysis. Barros et al (2014) assess the efficiency of audit firms in the United Kingdom (UK) using DEA. Hsiao et al (2014) assess the efficiency of accounting firms using DEA.…”
Section: Use Of Dea In the Accounting Literaturementioning
confidence: 99%
“…However, the study claimed, pointing out the decrease in economies of scale in all three countries, that increasing the production scale by M&As might not improve productivity. Barros et al (2014) also found, analyzing changes in productivity in UK accounting firms before and after the changes in the UK audit system in 2008, that changes in productivity were mixed before and after the regulation, regardless of the change.…”
Section: Previous Studiesmentioning
confidence: 94%
“…In response to changes in the international accounting environment, Korea has revised its related laws as well as introduced and applied new systems, markedly affecting the demand for and supply of the services provided by accounting firms (Barros, Couto, & Samagaio, 2014). Thus, to analyze the productivity of domestic accounting firms, one needs to understand the factors affecting the competition among them.…”
Section: Literature Review Accounting Regulatory Changes and Korean Amentioning
confidence: 99%
“…The later study focussed on the differences in impact of the ASAs on audit firms based on their size. Other regulatory aspects have also been examined, such as by Davis and Hay (2012) on the adequacy of audit self-regulation in New Zealand; Barros et al (2014) on the productivity change among auditing companies in the UK as a result of the European Statutory Audit Directive; Griffin et al (2009) on the impact of IFRS adoption on audit fees in New Zealand companies; Lee et al (2013) on how the mandatory designation rule affected audit fees charged and audit hours rendered by auditors for firms free from the mandatory rule in Korea; and Chang et al (2016b) on whether the audit partner disciplinary system in Taiwan helps to signal poor audit quality and enhance subsequent audit quality.…”
Section: Audit Regulationmentioning
confidence: 99%